2023
DOI: 10.1021/acsnano.3c00758
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Origin of Plasmon-Generated Hot Holes in Water Oxidation

Abstract: Plasmon-generated hot electrons in metal/oxide heterostructures have been used extensively for driving photochemistry. However, little is known about the origin of plasmon-generated hot holes in promoting photochemical reactions. Herein, we discover that, during the nonradiative plasmon decay, the interband excitation rather than the intraband excitation generates energetic hot holes that enable to drive the water oxidation at the Au/TiO 2 interface. Distinct from lukewarm holes via the intraband excitation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…The delayed A-M decay of interband excitation is quite insensitive to the specific morphology of the nanostructure under study and will be observed on a wide range of gold plasmonic systems. Therefore, the above discussion is relevant to the possible use of photogenerated hot d -holes in many gold plasmonic nanostructures for photocatalysis which has been proposed by a number of recent works: it is clear that the efficient use of d -holes requires an extremely rapid extraction of those carriers to the photocatalytic site as the extraction must compete with the ultrafast A-M process (as opposed to the possibly slower dynamics of electron thermalization). Furthermore, our results may be of importance for the understanding of whether or not and why interband excitation is more efficient than plasmonic excitation for photocatalytic purposes ,,, or indeed heating, , as suggested by recent publications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The delayed A-M decay of interband excitation is quite insensitive to the specific morphology of the nanostructure under study and will be observed on a wide range of gold plasmonic systems. Therefore, the above discussion is relevant to the possible use of photogenerated hot d -holes in many gold plasmonic nanostructures for photocatalysis which has been proposed by a number of recent works: it is clear that the efficient use of d -holes requires an extremely rapid extraction of those carriers to the photocatalytic site as the extraction must compete with the ultrafast A-M process (as opposed to the possibly slower dynamics of electron thermalization). Furthermore, our results may be of importance for the understanding of whether or not and why interband excitation is more efficient than plasmonic excitation for photocatalytic purposes ,,, or indeed heating, , as suggested by recent publications.…”
Section: Resultsmentioning
confidence: 99%
“…Direct interband excitation indeed generates large densities of highly energetic vacancies in the d -band, ,, whereupon the hot-electron generation by hot-hole Auger–Meitner decay heavily affects the lifetime of the photoexcited carriers and the possibility to exploit them for applications requiring high-energy photons. This is a critical aspect when exploiting hot-hole systems for catalytic purposes, as their extraction from metallic NPs has to compete with the ultrashort lifetimes of the Auger–Meitner process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the holes generated by the interband transition are more favorable to driving the H 2 O oxidation. 28,45–48…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, directly probing the local charge transfer processes of heterostructures at the nanoscale is of vital importance for the elucidation of their catalytic mechanisms. Previously, several analytical methods using transient absorption (TA), 16 in situ electron paramagnetic resonance (EPR), 17 photoluminescence (PL), 18 surface-enhanced Raman spectroscopy (SERS), 19 and Kelvin probe force microscopy (KPFM) 20 techniques have been utilized to characterize the plasmonic processes. However, most of these analytical methods still face challenges in probing the plasmon-enhanced electrocatalytic reactions in situ or at the nanoscale, and their implementation is complicated and time-consuming.…”
mentioning
confidence: 99%